2007
DOI: 10.1111/j.1460-9568.2007.05323.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide increases GABAergic mIPSC through presynaptic release of calcium from IP3 receptor‐sensitive stores in spinal cord substantia gelatinosa neurons

Abstract: GABAergic interneurons of the spinal cord substantia gelatinosa regulate the transmission of nociceptive information. Hydrogen peroxide (H2O2) is likely a diffusible messenger contributing to the development of long-lasting pathological pain states after nerve injury. In this study, we examined the presynaptic effects of H2O2 on the inhibitory interneurons of mouse substantia gelatinosa (SG) using whole-cell patch-clamp recordings from spinal cord slices. H2O2 increased the frequency of GABAergic miniature inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 58 publications
1
41
0
Order By: Relevance
“…The main presynaptic effect of H 2 O 2 in SG neurons is due to a presynaptic release of inositol-trisphosphate receptor-sensitive stored Ca 2+ [8]. This work reports on an atypical pharmacology exhibited by the p38 MAPK inhibitor SB203580, which blocks the postsynaptic effect of H 2 O 2 on the amplitude of mIPSCs.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The main presynaptic effect of H 2 O 2 in SG neurons is due to a presynaptic release of inositol-trisphosphate receptor-sensitive stored Ca 2+ [8]. This work reports on an atypical pharmacology exhibited by the p38 MAPK inhibitor SB203580, which blocks the postsynaptic effect of H 2 O 2 on the amplitude of mIPSCs.…”
Section: Introductionmentioning
confidence: 81%
“…SG neurons and a whole-cell patch-clamp recording were established as described [8]. The solution filling the pipette contained (in mM): 110 CsSO 4 , 0.5 CaCl 2 , 2 MgCl 2 , 5 TEACl, 5 ethylene glycol-bis (b-aminoethyl ether), 5 Mg adenosine triphosphatase, 5 N-2-hydroxyl piperazine-N′-2-ethane sulfonic acid, 270−290 mOsm/kg, pH 7.4.…”
Section: Electrophysiologymentioning
confidence: 99%
“…In addition, H2O2 stimulated glutamate release, elevation of [Ca 2+ ]c and ROS generation, which in turn led to neuronal cell death in cultured cortical cells [30]. A recent report demonstrated that H2O2 increased GABAergic mIPSCs through presynaptic release of Ca 2+ from inositol-1,4,5-trisphosphate receptor-sensitive Ca 2+ stores in the spinal cord substantia gelatinosa neurons [22]. In addition, several reports have demonstrated that cAMP-dependent PKA has an important role in certain conditions showing an increase in presynaptic GABA release in many neuronal preparations [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that the amount of GABA released from presynaptic terminals might be increased by H2O2, not through activation or inhibition of PKA, but through other mechanisms. From the results of a recent report [22], it can be suggested that the potentiating effect of H2O2 on the amount of GABA released from presynaptic terminals might be through IP3-induced presynaptic Ca 2+ increase. From the present study, it can be suggested that increased intracellular ROS of the neuronal nerve terminals of cerebral cortical neurons may increase the frequency and amount of GABA release from the presynaptic terminals and then inhibits the postsynaptic neuronal activity via increased GABAergic inhibitory synaptic transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation